The Inquisitor's Tongue : a Novel. - Singer, Alan (University of Alabama Press, 2012)
Alan Singer & rsquo;s riveting new novel, The Inquisitor & rsquo;s Tongue, reimagines the Spanish Inquisition as a world in which spiritual horrors and acts of violence are the birth pangs of otherwise unimaginable identities. The novel is the intersection of two narratives. The confession of Osvaldo Alonzo de Zamora, a miraculously gifted converso wine taster, is read aloud by a duplicitous priest of the Inquisition as an admonitory lesson to a suspected sinner. The competing narrative is the story of that sinner, another guilt-driven character, referred to only as the & ldquo;Samaritan, & rdquo.